An Analysis of Shot Types and Camera Angles in the Feature News "Transforming Scrap Fabric into Artwork" on the TVRI Jawa Barat News Program - Firman, Kania Nurrahmi; Nugroho, David Rizar (Lingkar Studi Komunikasi (LISKI), 2024)
"Transforming Scrap Fabric into Artwork" is one of the travel feature news segments aired on the TVRI Jawa Barat program, Jawa Barat Hari Ini (West Java Today). The primary focus of the feature news video is on the objects and locations of the tourist village being covered. The selection of appropriate filming techniques ensures that the information conveyed in the travel feature news is clear and effective for the audience. Therefore, it is essential to choose the right filming techniques to effectively highlight the uniqueness and inspirational story of Kampung Perca (Scrap Fabric Village). This research aims to analyze the filming techniques used in a feature news video, focusing on shot types and camera angles. Data collection methods include observation, interviews, and literature review. The data is analyzed through data reduction, data presentation, data validity testing, and conclusion drawing and verification. The shot types in the feature news video include six categories: wide shot/long shot, medium close-up, medium shot, close-up, big close-up, and over-the-shoulder shot. The camera angles used in the feature news video consist of three categories: high angle, low angle, and eye level. Keywords: angle camera; feature news; filming techniques; shot type.